Radiotherapy for pediatric adrenocortical carcinoma – Review of the literature. (July 2022) - Wiegering, Verena; Riedmeier, Maria; Thompson, Lester D.R.; Virgone, Calogero; Redlich, Antje; Kuhlen, Michaela; Gultekin, Melis; Yalcin, Bilgehan; Decarolis, Boris; Härtel, Christoph; Schlegel, Paul-Gerhardt; Fassnacht, Martin; et al.
Highlights: Radiotherapy (RT) is mostly performed for curative intent, only few cases in palliative setting are reported. The site of RT was predominantly tumor bed, abdominal cavity, and/or metastases. Adjuvant RT has to be discussed—even in the context of TPSs—especially for patients with high risk factors. Evidence regarding RT in in pediatric adrenocortical carcinoma is too limited to give any general recommendation. However, we suggest to consider adjuvant radiotherapy in individual patients with high risk of recurrence. A systematic international study with a common data platform is needed to establish evidence. on the role of RT in the treatment of children with adrenocortical carcinoma and to improve the outcome in this rare disease. Abstract: Background and purpose: Pediatric adrenocortical carcinoma (pACC) is a rare disease with poor prognosis. Publications on radiotherapy (RT) are scarce. This review summarizes the current data on RT for pACC and possibly provides first evidence to justify its use in this setting. Materials and methods: We searched the PubMed and Embase database for manuscripts regarding RT for pACC. Results: We included 17 manuscripts reporting on 76 patients treated with RT, after screening 2961 references and 269 full articles. In addition, we added data of 4 unreported pACC patients treated by co-authors. All reports based on retrospective data. Median age at first diagnosis was 11.1 years (70% female); 78% of patients presented with hormonal activity. RT was mostly performed for curative intent (78%). 88% of RT were administered during primary therapy. The site of RT was predominantly the local tumor bed (76%). Doses of RT ranged from 15 to 62 Gy (median 50 Gy). Information on target volumes or fractionation were lacking. Median follow-up was 6, 9 years and 64% of the patients died of disease, with 33% alive without disease. In 16 of 48 patients with available follow-up data after adjuvant RT (33%) no recurrence was reported and in 3 of 9 patients palliative RT seemed to induce some benefit for the patient. Conclusions: Our first systematic review on RT for pACC provides too few data for any general recommendation, but adjuvant RT in patients with high risk might be considered. International collaborative studies are urgently needed to establish better evidence on the role of RT in this rare malignancy.